2007
DOI: 10.1111/j.1462-5822.2006.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of community-associated methicillin-resistant Staphylococcus aureus exoproteins reveals molecules produced in vitro and during infection

Abstract: SummaryCommunity-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is a threat to human health worldwide. Although progress has been made, mechanisms of CA-MRSA pathogenesis are poorly understood and a comprehensive analysis of CA-MRSA exoproteins has not been conducted. To address that deficiency, we used proteomics to identify exoproteins made by MW2 (USA400) and LAC (USA300) during growth in vitro. Two hundred and fifty unique exoproteins were identified by 2-dimensional gel electrophoresis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 60 publications
4
109
0
4
Order By: Relevance
“…Mature 20-kDa SspB mimics plasma serine proteases as noted by its ability to (i) convert high molecular weight kininogen into heavy and light chains, (ii) hydrolyze the Bz-Pro-Phe-Arg substrate of kallikrein, a serine protease that processes single chain kininogen by excision of the vasoactive peptide bradykinin (RPPGFSPFR), (iii) process the N terminus of the fibrinogen ␤-chain at the same site as plasmin, and (iv) remove the N-terminal domain of fibronectin with a specificity equivalent to plasminogen activator (10). We have also found that antibodies to SspB are produced when mice are challenged with hypervirulent strains of community-acquired methicillin-resistant S. aureus and that SspA and SspB are rapidly expressed in neutrophil vacuoles following phagocytosis (11), alluding to a role in modifying vacuolar proteins.…”
mentioning
confidence: 68%
“…Mature 20-kDa SspB mimics plasma serine proteases as noted by its ability to (i) convert high molecular weight kininogen into heavy and light chains, (ii) hydrolyze the Bz-Pro-Phe-Arg substrate of kallikrein, a serine protease that processes single chain kininogen by excision of the vasoactive peptide bradykinin (RPPGFSPFR), (iii) process the N terminus of the fibrinogen ␤-chain at the same site as plasmin, and (iv) remove the N-terminal domain of fibronectin with a specificity equivalent to plasminogen activator (10). We have also found that antibodies to SspB are produced when mice are challenged with hypervirulent strains of community-acquired methicillin-resistant S. aureus and that SspA and SspB are rapidly expressed in neutrophil vacuoles following phagocytosis (11), alluding to a role in modifying vacuolar proteins.…”
mentioning
confidence: 68%
“…Aureolysin has been shown to contribute to 1) bacterial spreading and invasion by activating the fibrinolytic system (49), 2) resistance to antimicrobial peptides (26), and 3) inhibition of Ig production by lymphocytes (50). Recent studies suggested that aureolysin can be expressed within the phagocytic vacuole after phagocytosis of S. aureus (51). Furthermore it was shown that the isogenic aureolysin mutant was more efficiently killed by macrophages upon phagocytosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…All mutant strains were generated in an S. aureus MW2 background with in-frame deletion of target genes by allelic replacement, using the temperature-sensitive plasmid pMAD as described previously (15,30). S. aureus MW2 (USA400), a prototypical clinical methicillin-resistant S. aureus (MRSA) isolate, has been well characterized genotypically (e.g., available genome sequence information) and is virulent in vivo in animal models (31)(32)(33). Briefly, PCR was used to amplify an ϳ2-kb fragment comprising a 1-kb fragment upstream and another 1-kb fragment downstream of graS using genomic DNA as the template.…”
Section: Methodsmentioning
confidence: 99%